2000
DOI: 10.1007/s002130050023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine D 1-like and D 2-like agonists on cocaine self-administration in rhesus monkeys: rapid assessment of cocaine dose-effect functions

Abstract: The results suggest that D(1-like) and D(2-like) agonists produce qualitatively different effects on cocaine self-administration that may influence their usefulness for the treatment of cocaine abuse and dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 37 publications
8
59
0
Order By: Relevance
“…Studies focusing specifically on the dopamine D 2 receptor have typically reported an increase in D 2 receptor density following chronic exercise (Gilliam et al, 1984;MacRae et al, 1987). The D 2 receptor plays an important modulatory role in cocaine's reinforcing effects (Nader et al, 1999;Caine et al, 2000;Khroyan et al, 2000), and there is an increasing body of evidence that the reinforcing effects of psychomotor stimulants are inversely related to D 2 receptor density. For instance, in humans, the psychomotor stimulant methylphenidate is rated as less pleasurable and more aversive in people with high D 2 receptor density than in people with low D 2 receptor density (Volkow et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing specifically on the dopamine D 2 receptor have typically reported an increase in D 2 receptor density following chronic exercise (Gilliam et al, 1984;MacRae et al, 1987). The D 2 receptor plays an important modulatory role in cocaine's reinforcing effects (Nader et al, 1999;Caine et al, 2000;Khroyan et al, 2000), and there is an increasing body of evidence that the reinforcing effects of psychomotor stimulants are inversely related to D 2 receptor density. For instance, in humans, the psychomotor stimulant methylphenidate is rated as less pleasurable and more aversive in people with high D 2 receptor density than in people with low D 2 receptor density (Volkow et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The acute effects of mixed mu/kappa agonists on cocaine's reinforcing and discriminative stimulus effects have been less consistent. In a drug self-administration procedure where treatment drug effects on multiple unit doses of cocaine could be evaluated in two or three sessions (Caine et al, 2000), the mixed mu/ kappa agonists (脌)cyclorphan, Mr2034, and MCL-101 dose dependently decreased cocaine self-administration with minimal side effects (Bowen et al, 2003). However, acute administration of the same mixed mu/kappa agonists that reduced cocaine self-administration did not significantly attenuate cocaine discrimination, and did not produce rightward shifts in the cocaine discrimination dose-effect curve in rhesus monkeys (Negus and Mello, 1999;Bowen et al, 2003).…”
Section: Kappa Opioid-cocaine Interactionsmentioning
confidence: 99%
“…The D1 receptor plays a critical role in mediating the behavioral and cellular effects of cocaine. For example, D1 receptor agonists and antagonists can affect cocaine-induced locomotor responses, discriminative stimulus, reinforcing effects, and reinstatement in a variety of experimental animal systems (Cabib et al, 1991;Caine and Koob, 1994;Tella, 1994;Cervo and Samanin, 1995;Pruitt et al, 1995;Self et al, 1996;Grech et al, 1996;Baker et al, 1998;Tzschentke, 1998;Caine et al, 1999Caine et al, , 2000Katz et al, 1999;Khroyan et al, 2000;Anderson et al, 2003;Nazarian et al, 2004). Repeated cocaine injections also lead to persistent increases in D1 receptor sensitivity within the NAc (Henry and White, 1995).…”
Section: Introductionmentioning
confidence: 99%